2021
DOI: 10.1101/2021.10.23.465439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The challenges of independence: ontogeny of at-sea behaviour in a long-lived seabird

Abstract: The transition to independent foraging represents an important developmental stage in the life cycle of most vertebrate animals. Juveniles differ from adults in various life history traits and tend to survive less well than adults in most long-lived animals. Several hypotheses have been proposed to explain higher mortality including that of inadequate/inferior foraging skills compared to adults, young naive individuals combining lack of experience and physical immaturity. Thus a change in behaviour, resulting … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 113 publications
(187 reference statements)
0
3
0
Order By: Relevance
“…Immature Great Shearwaters are not yet on an annual schedule to breed, and thus might choose an energetically easier path by leaving later. Younger birds may also be slower in acquiring reserves to migrate (Delord et al, 2021), and/or have no selective advantage of migrating earlier to compete with adults at foraging areas in the S Atlantic. Differential foraging strategies and segregation in trophic niches exist between breeders and immatures in procellariids (Riotte-Lambert and Weimerskirch, 2013;Campioni et al, 2016) Wind Interactions Along Migration central place foraging (Riotte-Lambert and Weimerskirch, 2013), or developmental shift in prey selection (Campioni et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Immature Great Shearwaters are not yet on an annual schedule to breed, and thus might choose an energetically easier path by leaving later. Younger birds may also be slower in acquiring reserves to migrate (Delord et al, 2021), and/or have no selective advantage of migrating earlier to compete with adults at foraging areas in the S Atlantic. Differential foraging strategies and segregation in trophic niches exist between breeders and immatures in procellariids (Riotte-Lambert and Weimerskirch, 2013;Campioni et al, 2016) Wind Interactions Along Migration central place foraging (Riotte-Lambert and Weimerskirch, 2013), or developmental shift in prey selection (Campioni et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Data supporting the results are available at https://doi.org/10.6084/m9.figshare.25260310 (Delord et al, 2024a). Supplementary material is available at https://doi.org/10.6084/m9.figshare.25289098 (Delord et al, 2024b).…”
Section: Data Code and Supplementary Materials Availabilitymentioning
confidence: 94%
“…So far, cross-sectional studies have hypothesized (and mostly confirmed) that foraging performance increases with age, at least in the younger age classes (e.g. [5][6][7]). This might be due to the selective disappearance of under-performing individuals rather than, or in addition to, learning maturation processes.…”
Section: Introductionmentioning
confidence: 96%